2014
DOI: 10.5121/ijcsea.2014.4202
|View full text |Cite
|
Sign up to set email alerts
|

Study of Effectiveness of Time Series Modeling (Arima) in Forecasting Stock Prices

Abstract: Stock price prediction has always attracted interest because of the direct financial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(137 citation statements)
references
References 16 publications
3
98
0
6
Order By: Relevance
“…Finally, the ARIMA(p,d,q) which is a generalization of ARMA(p,q) is mathematically defined as in (14)  …”
Section: Formulation Of Autoregressive Integrated Moving Average mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the ARIMA(p,d,q) which is a generalization of ARMA(p,q) is mathematically defined as in (14)  …”
Section: Formulation Of Autoregressive Integrated Moving Average mentioning
confidence: 99%
“…The existing literature contains numerous forecast models such as Exponential Smoothing (ETS) [11], TBATS model [12] and Autoregressive and Moving Average (ARMA) model [13]. ARMA model is a well-known method to investigate the time series data [14]. Based on ARMA model, [15] formulated Autoregressive and Integrated Moving Average (ARIMA) model for predicting the linear time series data by transforming the non-stationary data into stationary data before forecasting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used to quantify the goodness of fit of the model. When comparing two or more models, the one with the lowest AIC is generally considered to be closer with real data (Mondal et al, 2014;p.15).…”
Section: Graph 2 Time Series Plots Of the Variablesmentioning
confidence: 99%
“…Autoregressive integrated moving average (ARIMA) models were proposed by Box and Jenkins (1970) for time series analysis and forecasting. Some studies have been conducted by employing ARIMA models to forecast stock market returns (Al-Shaib, 2006;Ojo and Olatayo, 2009;Adebiyi and Oluinka, 2014;Mondal et al, 2014). Quite a few studies found that ARIMA models produced inferior forecasts for financial time series data (Zhang, 2003;Adebiyi and Oluinka, 2014;Khandelwal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%